THE RELATIONSHIP BETWEEN FOREIGN PORTFOLIO INVESTMENT AND MACROECONOMIC VARIABLES - Guluzar Kurt Gumus; Atakan Duru; Bener Gungor (European Scientific Journal, ESJ, 2013)
The study analyzes the relationship between foreign portfolio investments and macroeconomic factors for the period between 2006-2012 by using VAR, Var Granger Causality Tests, Impulse Responses and Variance Decomposition. According to Granger Causality Tests and Impulse Responses, foreign portfolio investment affects Istanbul Stock Exchange Price Index and exchange rates. Only industrial production index has affect on foreign portfolio investment.